Africa, democracy put to the test - (:unkn) unknown (My University, 2022)
Africa votes massively. There have been six hundred and thirty presidential and legislative elections since 1990 on the continent. But can we therefore take democracy for granted? The manipulation of the polls remains frequent, the disputes of the results are followed by social tensions, the mandates are not respected. But governance is also approximate, fundamental freedoms fragile: it is therefore above all "substantial democracy" that is generally lacking, apart from a few edifying experiences. Based on a synthesis of numerous works and his own experience, the former diplomat, today essayist and academic Pierre Jacquemot sheds light on three decades of political evolution, painting the portrait of an Africa with contrasting configurations and challenged new societal dynamics “outside the ballot box” stemming from civil society. Are some heralds of other ways of governing?
Keywords: African Research